Job satisfaction of secondary school teachers in Tawau, Sabah - Abdullah, Muhammad Madi; Uli, Jegak; Salahudin, Shahrul Nizam (2007)
In order for the teachers to function effectively in a school system, it is important that teachers need to seek satisfaction and happiness not only in the intrinsic aspects of teaching job but also in other dimensions related to the teacher work experience in the wider social environment. This paper examines the level and differences in the job satisfaction of 200 Sabah secondary school teachers with respect to the various teachers characteristics identified as gender, service category, job title, tenure and place of origin. Data was collected through survey questionnaire. The finding reveals that secondary school teachers in Tawau, Sabah are generally satisfied with their job. There is significant relationship between job satisfaction and gender, whereby the male teachers are generally more satisfied than female teachers. The graduate teachers are more satisfied than non-graduate teachers. The higher ranking teachers are more satisfied than the ordinary teachers. Also, older teachers are more satisfied than younger teachers. However, there is no significant relationship between places of origin of teachers with job satisfaction. Based on the findings, several recommendations are proposed.